1993
DOI: 10.3109/10425179309015618
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence of the glucosyltransferase gene of serotype dStreptococcus sobrinus

Abstract: A glucosyltransferase (GTF) gene was cloned into Escherichia coli from serotype d Streptococcus sobrinus OMZ176. Transformed E. coli strain MI expressed water-insoluble glucan synthesizing activity. Restriction enzyme map of pGT31 extracted from MI shows that the enzyme gene exists in the 6.4-KB PstI-fragment inserted into pBR322 vector. DNA sequence analysis indicates that a single ORF (530-5,300) is located in the PstI-fragment. The putative amino-acid composition (1,590 residues) resembles those of other GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…that of S. sobrinus 6715. The first 38 amino acids contained the signal sequence of GTF proteins, and these amino acids were similar to those by previously reported GTFs (Ferretti et al, 1987;Shiroza et al, 1987;Abo et al, 1991;Sato et al, 1993). Then, Mooser et al (1991) reported the putative active-site sequence (DSIRDAVD) from GTF-I enzyme of S. sobrinus 6715, and the corresponding sequence was identified in the amino acid sequence of S. orisuis JCM14035.…”
Section: (A ) (B)mentioning
confidence: 69%
“…that of S. sobrinus 6715. The first 38 amino acids contained the signal sequence of GTF proteins, and these amino acids were similar to those by previously reported GTFs (Ferretti et al, 1987;Shiroza et al, 1987;Abo et al, 1991;Sato et al, 1993). Then, Mooser et al (1991) reported the putative active-site sequence (DSIRDAVD) from GTF-I enzyme of S. sobrinus 6715, and the corresponding sequence was identified in the amino acid sequence of S. orisuis JCM14035.…”
Section: (A ) (B)mentioning
confidence: 69%
“…Studies initiated more than 10 years ago allowed the isolation and sequencing of 17 genes coding for glucansucrases produced by oral streptococci involved in the cariogenesis process, S. mutans GS5 or LM7, S. sobrinus serotype h ( S. downei Mfe28), serotype g ( S. sobrinus 6715), serotype d ( S. sobrinus OMZ176), by S. salivarius ATCC 25975 and by L. mesenteroides NRRL B‐512F and B‐1299 (Table 1) [12–36]. Isolated glucansucrases are all large enzymes with an average M r of 160 000.…”
Section: Structural and Functional Organisation Of The Glucansucrasesmentioning
confidence: 99%
“…Isolated glucansucrases are all large enzymes with an average M r of 160 000. Streptococci glucansucrases synthesise primarily α(1–3) rich mutan polysaccharides and α(1–6) rich dextran polysaccharides [12–33]. L. mesenteroides glucansucrases produce α(1–6) rich dextrans [34–36, 84].…”
Section: Structural and Functional Organisation Of The Glucansucrasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the significant ecological roles of GTF enzymes and their glucan products, little is known about their regulation. The mutans streptococci and Streptococcus salivarius have multiple GTF enzymes coded for by multiple gtf genes (3,8,9,12,24,25,30). No genetic regulatory mechanisms for these gtf genes have been described.…”
mentioning
confidence: 99%